Long-term fertilizer application and cover crops improve soil quality and soybean yield in the Northeastern Pampas region of Argentina - Fontana, Marianela B.; Novelli, Leonardo Esteban; Sterren, María A.; Uhrich, Walter G.; Benintende, Silvia M.; Barbagelata, Pedro Anibal (Elsevier, 2021)
Long-term improvements in soil quality through cover crops (CC) and fertilizer management may provide resilience for temporal water stresses in cropping sequences based on soybean [Glycine max (L.) Merr.]. The objectives of this work were: i) to evaluate the combined effects of CC and fertilizer use on soil properties and ii) to relate soil properties with soybean grain yield in different cropping sequences and contrasting rainfall regimes. Six treatments, combining cropping sequences – fertilization strategy, were studied: soybean monocropping (Sy), fertilized soybean monocropping (Syf), CC/soybean (CC/Sy), CC/fertilized soybean (CC/Syf), N-fertilized CC/fertilized soybean (CCN/Syf), and N-fertilized CC/fertilized soybean in a crop rotation of CCN/Syf-wheat/soybean - maize (CCN/Syf rot). Soil samples were collected in 2015 and 2016 from the 0–5 and 0–15 cm depth intervals, in a long-term field experiment under no-tillage in Paraná, Argentina. Soybean grain yield and soil properties were determined. In both depths, all soil properties increased in treatments that included winter CC (except for CC/Sy). In addition, the soybean yield was 15% greater in treatments that included winter CC and fertilizer use than in monocropping treatments. The CC/Sy treatment performed similarly to soybean monocropping. Under more favorable rainfall conditions, only the soybean yield in CC/Sy was reduced. However, under unfavorable rainfall conditions, the negative effects of the soybean monoccropping were mitigated including CC and fertilization. Significant positive correlations (P < 0.05) between soybean yield and soil properties were found in the average rainfall season, mainly in the 0–5 cm depth. The study highlights the importance of combining high cropping intensity with adequate fertilizer use to maintain or improve the soil quality and, consequently, the soil resilience under reduced water availability.